Human milk benefits and breastfeeding - Fani Anatolitou (Hygeia Press di Corridori Marinella, 2012)
Human milk is uniquely superior for infant feeding and represents the perfect example of individualization in Pediatrics. Human milk is not a uniform body fluid but a secretion of the mammary gland of changing composition. Foremilk differs from hindmilk, and colostrum is strikingly different from transitional and mature milk. Milk changes with time of day and during the course of lactation. Extensive research has demonstrated health, nutritional, immunologic, developmental, psychological, social, economic and environmental benefits of human milk. Breastfeeding results in improved infant and maternal health outcomes in both the industrialized and developing world. Some specific topics will be discussed such as the preventive effect of human milk on infections, overweight, obesity and diabetes, malignant disease, neurodevelopmental outcomes, reduction of necrotizing enterocolitis. Important health benefits of breastfeeding and lactation are also described for mothers. Finally, contraindications to breastfeeding and supplementation of breastfed infants are presented. Interventions to promote breastfeeding are relatively simple and inexpensive. Infant feeding should not be regarded as a lifestyle choice but rather as a basic health issue.